Literature Review: Pengaruh Neuromuscular Electrical Stimulation (NMES) terhadap Spastisitas Pasca Stroke - Meilina Nur Hafizah; Muhammad Siddik; Pagan Pambudi (Homeostasis, 2021)
Abstract: Spasticity is one of the post-stroke symptoms that can cause nuisance and also functional problems. Neuromuscular Electrical Stimulation (NMES) is medical rehabilitation using a methods that modify neuromuscular activity. The purpose of this literature review is to determine the effect of NMES on reducing spasticity in post-stroke patients, to determine the effect of NMES combined with other methods on reduction of post-stroke spasticity, and to analyze the effect of NMES on post-stroke spasticity. This study was done by analyzing sources from several medical journal databases from 2010-2020, such as PubMed, Science Direct, and Google Scholar. The results of this study indicate the effect of NMES on the improvement of patient post-stroke spasticity, whether it combined or not. In addition, NMES in combination with other interventions not only has an effect on improving spasticity, but also can help maximize functional improvements. Keywords: neuromuscular electrical stimulation, stroke, spasticity. Abstrak: Spastisitas merupakan salah satu gejala pasca stroke yang dapat menyebabkan gangguan serta masalah fungsional. Neuromuscular Electrical Stimulation (NMES) merupakan rehabilitasi medis dengan menggunakan metode penerapan yang dapat memodifikasi aktivitas neuromuscular. Tujuan literature review ini untuk mengetahui pengaruh NMES terhadap penurunan spastisitas pada pasien pasca stroke, mengetahui pengaruh NMES yang dikombinasikan dengan metode lain terhadap penurunan spastisitas pasca stroke, dan menganalisis pengaruh NMES terhadap spastisitas pasca stroke. Penulisan ini dilakukan dengan menganalisis sumber pustaka dari beberapa database jurnal kedokteran dari tahun 2010-2020, yaitu PubMed, Science Direct, dan Google Scholar. Hasil penulisan ini menunjukkan adanya pengaruh NMES pada perbaikan pasien spastisitas pasca stroke, baik itu yang dikombinasikan maupun tidak. Selain itu, NMES yang dikombinasikan dengan intervensi lain tidak hanya berpengaruh pada perbaikan spastisitas saja, tetapi juga dapat membantu perbaikan fungsional yang lebih maksimal. Kata-kata kunci: neuromuscular electrical stimulation, stroke, spasticity.